Dispositional optimism as a buffer against emotional reactivity to daily stressors: A daily diary approach - MAJEED, Nadyanna (Institutional Knowledge at Singapore Management University, 2021)
The current research examined if dispositional optimism buffers against the negative influences of daily stressors on affective experiences, using a daily diary study of two large and nationally-drawn samples of American adults (N = 2,349). Optimism, exposure to daily stressors, and daily positive and negative affect were assessed over eight days. Multilevel modelling revealed that optimism significantly attenuated the associations between daily stressor exposure and negative affect reactivity even after controlling for demographic factors, subjective physical health, and socioeconomic status. However, in a similar analysis, the inclusion of socioeconomic variables fully accounted for the moderating effect of optimism on stress and positive affect reactivity. The findings suggest distinct processes that are involved in how optimism reduces daily stress reactivity.